Low programmed cell death-1 (PD-1) expression in peripheral CD4+ T cells in Japanese patients with autoimmune type 1 diabetes. (15th May 2015) - Fujisawa, R; Haseda, F; Tsutsumi, C; Hiromine, Y; Noso, S; Kawabata, Y; Mitsui, S; Terasaki, J; Ikegami, H; Imagawa, A; Hanafusa, T
Summary: Programmed cell death-1 (PD-1) is a co-stimulatory molecule that inhibits T cell proliferation. We aimed to clarify PD-1 expression in CD4 + T cells and the association between PD-1 expression and the 7785C/T polymorphism of PDCD1, with a focus on the two subtypes of type 1 diabetes, type 1A diabetes (T1AD) and fulminant type 1 diabetes (FT1D), in the Japanese population. We examined 22 patients with T1AD, 15 with FT1D, 19 with type 2 diabetes (T2D) and 29 healthy control (HC) subjects. Fluorescence-activated cell sorting (FACS) and real-time PCR were utilized to analyse PD-1 expression quantitatively. Genotyping of 7785C/T in PDCD1 was performed using the TaqMan method in a total of 63 subjects (21 with T1AD, 15 with FT1D and 27 HC). FACS revealed a significant reduction in PD-1 expression in CD4 + T cells in patients with T1AD (mean: 4·2 vs. 6·0% in FT1D, P = 0·0450; vs. 5·8% in T2D, P = 0·0098; vs. 6·0% in HC, P = 0·0018). PD-1 mRNA expression in CD4 + T cells was also significantly lower in patients with T1AD than in the HC subjects. Of the 63 subjects, PD-1 expression was significantly lower in individuals with the 7785C/C genotype than in those with the C/T and T/T genotypes (mean: 4·1 vs. 5·9%, P = 0·0016). Our results indicate that lower PD-1 expression in CD4 + T-cells might contribute to the development of T1AD through T cell activation.